Interprofessional education—situations of a university in Hong Kong and major hurdles to teachers and students - Li, Joyce T. S.; Chau, Janita P. C.; Wong, Samuel Y. S; Lau, Ann S. N.; Chan, Wallace C. H.; Yip, Peggy P. S.; Yang, Yijian; Ku, Fred K. T.; Sze, Felix Y. B.; King, Irwin K. C.; Lee, Vivian W. Y. (Frontiers in Education, 2022)
Studies have provided evidence that Interprofessional Education (IPE) can improve learners’ attitudes, knowledge, skills, behaviours, and competency. Traditionally, IPE is commonly seen in the healthcare professional training in tertiary education. Ageing is a global issue that requires beyond a single healthcare sector. It requires interdisciplinary collaboration and understanding to tackle the issues. Therefore, IPE is essential for nurturing university students to tackle the ever-changing global challenges. Yet, different hurdles can hinder IPE development. In order to have better understanding of the feasibility, acceptance, and educational value of IPE in Hong Kong, we conducted a cross-sectional quantitative study. We invited teachers and students from a Hong Kong university to fill in an online survey that evaluated their understanding and participation in IPE, their attitude towards IPE, and the barriers of developing IPE. Among the 37 academic staff and 572 students who completed the survey, 20 (54.1%) teachers and 422 (73.8%) students had never heard of IPE before, and 26 (70.3%) teachers and 510 (89.2%) students had never participated in any IPE activities. Major barriers reported by teachers included increase in teaching load (72.9%), lack of administrative support (72.9%), lack of financial support and limited budget (67.5%), difficult to make logistic arrangements (64.8%), and problems with academic schedule and calendar (62.1%). The survey findings revealed that despite the positive attitude of university teachers and students towards IPE, barriers could hinder the development of IPE included heavy teaching and administrative load and logistic arrangement for classroom arrangement and academic scheduling involving multiple faculties.